1989
DOI: 10.1071/ar9890419
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Haemonchus contortus on liveweight gain and wool growth in young merino sheep

Abstract: Results of three crossover experiments on a total of 1078 Merino lambs were used to estimate the effect of a single infection of 11 000 Haernonchus contortus larvae on liveweight gain, clean wool growth and wool fineness. Estimates were obtained by direct comparison of six groups of infected and matched uninfected iambs under field conditions. Infections were terminated after 5 weeks, at which stage some mortality had occurred and haematocrits had in five out of six cases declined to less than 24%. Over an 8-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Albers et al (1989) concluded that there was a lag phase of at least 3 weeks between actual infection and the onset of the effect of infection on wool growth, while the maximum effect was seen at 9 to 10 weeks p.i. Due to variation in the length of the wool growth recording periods across years (see Albers et al, 1989), wool growth periods in the three experiments did not match nor was it possible to calculate clean wool growth for the entire 'affected period'. Due to variation in the length of the wool growth recording periods across years (see Albers et al, 1989), wool growth periods in the three experiments did not match nor was it possible to calculate clean wool growth for the entire 'affected period'.…”
Section: Table 3 Linear Regression Of Live-weight Gain (Lwg) (Infectimentioning
confidence: 99%
See 1 more Smart Citation
“…Albers et al (1989) concluded that there was a lag phase of at least 3 weeks between actual infection and the onset of the effect of infection on wool growth, while the maximum effect was seen at 9 to 10 weeks p.i. Due to variation in the length of the wool growth recording periods across years (see Albers et al, 1989), wool growth periods in the three experiments did not match nor was it possible to calculate clean wool growth for the entire 'affected period'. Due to variation in the length of the wool growth recording periods across years (see Albers et al, 1989), wool growth periods in the three experiments did not match nor was it possible to calculate clean wool growth for the entire 'affected period'.…”
Section: Table 3 Linear Regression Of Live-weight Gain (Lwg) (Infectimentioning
confidence: 99%
“…low P lasma iron concentrations then signals Dargie and Allonby (1975) studied red cell final exhaustion of the parasitized sheep, kinetics in infected sheep using radio-isotopic Albers and Le ,, Jambre ^f) m u a similar methods. In these experiments, the effect of H. contortus infection on live-weight gain (LWG) and wool growth was determined (Albers, Gray, Le Jambre, Piper, Barger and Barker, 1989) and the present paper describes the relationship between the pathogenic effects of infection as determined by haematological parameters, and production characters. Furthermore, they established relatively small.…”
mentioning
confidence: 99%
“…However, challenge protocols are still needed in order to phenotype sheep as resistant or susceptible. This continuous validation of improved resistance is usually performed on weaned lambs to reduce generation intervals, but these procedures also suppress lamb production [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Barger, citado por Albers et al (1989), o parasita Haemonchus contortus promove grandes perdas na produção ovina em regiões onde calor e umidade ocorrem simultaneamente. No entanto, a região noroeste do estado de São Paulo apresenta condições climáticas muito semelhantes à região Centro-Oeste do Brasil, apresentando uma estação quente e chuvosa (outubro a abril) e outra (maio a setembro) seca e com temperatura mais amena, que coincide com o nascimento e a terminação dos cordeiros de raças sazonais, evitando que sofram os efeitos da verminose e permitindo sua manutenção em pastagem.…”
Section: Introductionunclassified